Memory-Guided Video Scene Understanding for Embodied AI Navigation and Interactive Perception (International Journal of Artificial Intelligence Engineering and Systems, 2026)
Embodied artificial intelligence systems that operate in dynamic real-world environments must continuously parse streaming visual information, retain context over extended temporal horizons, and adapt their behavior in response to changing scenes. This paper presents a system-level analysis of memory-guided video scene understanding as a foundational capability for embodied navigation and interactive perception. We examine the architectural space of memory mechanisms—ranging from differentiable external stores and episodic controllers to transformer-based long-range context models—and trace their integration into video understanding pipelines that serve navigation, manipulation, and multimodal reasoning. Rather than focusing on algorithmic novelty, the discussion foregrounds structural trade-offs in capacity, retrieval latency, training stability, and deployment footprint, and it situates these technical considerations within broader sociotechnical frameworks. The paper dissects the interplay between spatial-topological mapping, object-centric memory, and continual adaptation in navigation tasks, and it extends the analysis to interactive perception where memory of past interactions shapes affordance learning and task planning. System-level challenges are then explored, including edge-cloud partitioning, energy efficiency, robustness under sensor degradation, and the tension between persistent memory and privacy. Governance, fairness, and safety implications are addressed through the lenses of bias auditing, regulatory compliance, and inclusive design, emphasizing that memory-guided embodied agents straddle the boundary between high-stakes autonomy and socially embedded operation. By synthesizing architectural insights with deployment and policy perspectives, the paper provides a holistic reference for researchers, system architects, and policymakers engaged in the development of trustworthy embodied AI.
Keywords: embodied AI, video scene understanding, memory architectures, visual navigation, interactive perception, system design, fairness, governance